Mut‘ah Marriage among Migrant Workers: A Socio-Legal and Maqāṣid al-Sharī‘ah Analysis - Cut Rizky Meutia; Zidan Tri Luca Aditama (Tabayyanu : Journal Of Islamic Law, 2025)
The phenomenon of mut‘ah marriage among migrant workers reflects a contemporary problem in Islamic family law that can no longer be understood merely as a classical juristic debate. Labor mobility, prolonged family separation, and socio-economic vulnerability have encouraged the practice of mut‘ah marriage as a form of rationalization for the biological and emotional needs of migrant workers. This study aims to analyze the practice of mut‘ah marriage through a socio-legal and maqāṣid al-sharī‘ah approach in order to examine the relationship between legal norms, social realities, and the protection of family institutions. The study employs an empirical legal method with a socio-legal approach by integrating Islamic law, Indonesian positive law, and empirical studies related to migrant workers and mut‘ah marriage. The findings reveal that mut‘ah marriage not only raises issues of legal validity but also creates structural vulnerabilities for women and children due to the absence of adequate legal protection. From the perspective of maqāṣid al-sharī‘ah, the practice contradicts the principles of ḥifẓ al-nasl and ḥifẓ al-‘irḍ because it reduces marriage to a temporary and transactional relationship. This study further finds that mut‘ah marriage develops within a gray area between religious law, state law, and the social needs of migrant workers. The article argues that mut‘ah marriage should be positioned as a socio-legal and family resilience issue rather than merely a juristic disagreement.